The study of marginal deformations of the leaf extracts with regard to plastic thinning and destruction of the material - Yury A. Morozov (Structural Mechanics of Engineering Constructions and Buildings, 2019)
The aim of work. The paper analyzes the process of sheet drawing and develops a method for determining the minimum curvature of the torus fillet in the formation of a cylindrical product (glass), taking into account the plastic thinning of the deformable material by the end edge of the pressing punch. Methods. The existing scheme of forming with the use of permissible coefficients of drawing and tensile strength of the material, representing the basis of deformation-force calculation, which often ignores the factor of deformation thinning and its impact on the strength of the material, which together can lead to excess of the allowable stress in the material, causing its rupture, is analyzed. A mathematical model of the volume stress state of the metal is developed, which allows to estimate the value of the thinning in the formation of the torus surface of different curvature, followed by the approximation of the values found by a polynomial function. Considering the criterion of limit loads the level of radial stresses during folding and stretching of the sheet material, taking into account its thinning, the minimum curvature of the torus surface of the glass is established. Results. The results obtained will allow to simulate the stress-strain state of the metal in the development of sheet drawing technology: to establish the value of thinning and to estimate the level of radial stresses in the formation of the torus surface rounding to prevent the destruction of the elongated glass (separation of the bottom), which guarantees quality products.